Characteristics of adults with overweight/obesity and high internal disinhibition: do they fit with targets for acceptance‐based interventions?. (14th March 2017) - Niemeier, H. M.; Lillis, J.; Wing, R. R.
Summary: Objective: Adults with overweight/obesity reporting high levels of internal disinhibition (ID) tend to do poorly in standard behavioural weight loss programmes. The current study sought to compare a sample of individuals with overweight/obesity selected on the basis of high ID with an unselected treatment‐seeking sample of adults with overweight/obesity on characteristics that might make acceptance‐based treatments particularly appropriate for those with high ID. Methods: Sample 1 included 162 treatment‐seeking adults with overweight/obesity who were selected for high ID; sample 2 included 194 unselected treatment‐seeking adults with overweight/obesity. First, the two samples were compared on levels of general and weight‐related experiential avoidance, and values‐consistent behaviour, both of which are targeted in acceptance‐based treatments, and on other general psychological characteristics. Next, the unselected sample was split into two groups, those meeting criteria for high ( N  = 105; sample 2/high ID) vs. low ( N  = 89; sample 2/low ID) ID, and the three groups were compared on the same characteristics. Results: Sample 1 reported higher levels of both general and weight‐related experiential avoidance as well as less values‐consistent behaviour than sample 2. They reported greater psychological impairment in quality of life, depression and anxiety. Within sample 2, 54% met the criteria for high ID. Both sample 1 and sample 2/high ID reported higher levels of experiential avoidance and less values‐consistent behaviour than did the sample 2/low ID. The two high ID samples also reported greater psychological impairment in quality of life, depression and anxiety than sample 2/low ID. Conclusions: Adults with overweight/obesity who report high levels of ID were characterized by higher levels of experiential avoidance, lower levels of values‐consistent behaviour, and more psychosocial impairment as compared with other adults with overweight/obesity. As these are important targets of acceptance‐based approaches, this subgroup may benefit from the integration of such approaches into behavioural weight loss programmes.